PENGARUH KUALITAS LAYANAN DAN CITRA PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN CONATO BAKERY GAJAH MADA JEMBER - Dindin Aldila Kustantia; Nurul Qomariah; Akhmad Fahrur Rozi (Universitas Bandar Lampung (UBL), 2021)
The current economic development is increasingly leading to fierce competition, especially for similar companies or businesses. This makes the competition between companies even tighter in the struggle for market share. Every company wants to be successful in running its business. One company that is experiencing intense competition with other similar companies is a bakery company. The purpose of this study is to determine and analyze the effect of service quality and product image on purchasing decisions partially. The population in this study were consumers of